Analysis of Digital Maturity Aspects in Hospitals: A Systematic Literature Review - Nurhayati, Siti; Suratman; Ngadiman (International Journal of Science and Society, 2025)
Hospitals must continuously evolve in response to dynamic environments and rapidly changing demands. Digital transformation plays a pivotal role in reducing costs, increasing speed and transparency, and enhancing productivity and efficiency; however, it simultaneously introduces substantial organizational risks. Frameworks and tools are therefore essential to support organizations in navigating such profound transitions. Digital maturity assessment constitutes a critical preliminary stage for any digital transformation initiative, enabling both public and private healthcare institutions to determine their level of digital maturity and establish a foundation for subsequent transformation efforts. This study aims to identify and describe the dimensions applied in digital maturity assessments within hospitals. The research employed a systematic literature review of peer-reviewed publications from 2020 to 2024, examining maturity models designed to evaluate hospital digital maturity. A total of 29 relevant articles were reviewed, synthesizing 27 distinct maturity models. The articles were subjected to inductive analysis, through which the dimensions of maturity models were extracted and synthesized into a comprehensive digital maturity framework. The findings revealed a digital maturity framework consisting of seven dimensions: strategy, information technology capabilities, interoperability, governance and management, patient-centered care, human resource skills and behaviors, and data analytics. Each of these seven dimensions can be assessed through 24 specific indicators. The study concludes that the proposed digital maturity framework can serve as an evaluative tool for assessing hospital digital maturity and identifying critical areas for improvement.